Motion artefact in voltage-sensitive fluorescent dye emission during repeated ischemia of isolated heart - Janoušek, O; Kolářová, J; Ronzhina, M; Nováková, M; Provazník, I (Physiological research, 2013)
Motion artefact (MA) in voltage-sensitive fluorescent signals causes significant debasement of action potential. During ischemia and reperfusion in isolated rabbit heart, this artefact develops in a manner which may be described by the time of its onset, level, and shape. The MA during ischemia: (a) may become substantial with approximately two minutes delay after establishing global ischemia; (b) may be almost twice as high as the physiological action potential and decreases both with time and repetition of ischemia; (c) the MA shape is unpredictable and depends on individual rabbit.
Keywords: Myocardial Reperfusion Injury; reperfuzní poškození myokardu; Artifacts; králíci; Action Potentials; Voltage-Sensitive Dye Imaging; perfuze; prediktivní hodnota testů; pyridinové sloučeniny; artefakty; Fluorescent Dyes; Time Factors; zvířata; Animals; Predictive Value of Tests; zobrazování pomocí barviva citlivého na potenciál; časové faktory; fluorescenční barviva; akční potenciály; techniky in vitro; Rabbits; In Vitro Techniques; Pyridinium Compounds; Perfusion